Climatological summaries of Thomas Hughes' meteorological data, for Stroud, UK (1775–1813). (28th February 2020) - Harrison, Richard Giles; Harrison, Barry C.
Abstract: Thomas Hughes (1742–1813) kept a daily diary of weather and geoscience phenomena at Stroud in Gloucestershire, in the southern UK, between 1775 and 1813, following a short period of similar records made nearby from 1771. Data from the diary have previously been used in compiling the Central England Temperature series and to corroborate aurora sightings elsewhere in Europe. Recent historical research now confirms the suspected authorship of the diaries beyond doubt and strongly suggests that the pre‐Stroud records were made in south Gloucestershire. Here, summary tables of monthly data between 1771 and 1813 are presented for thunderstorm days, snow days, rain days, rainfall, surface air pressure and auroral nights. Consistency checks, both between the different measurements contained and with other contemporary measurements, provide confidence in the reliability of the meteorological and geophysical data which spans part of the Dalton Minimum in solar activity. Abstract : Data from a daily diary of weather and geoscience phenomena at Stroud, UK between 1775 and 1813 are presented. Recent research confirms Thomas Hughes as the diarist beyond doubt. Summary tables of monthly data between 1771 and 1813 are presented for thunderstorm days, snow days, rain days, rainfall, surface air pressure and auroral nights.